STRATEGI DAN EFEKTIVITAS KOMUNIKASI CSR PT. VALE INDONESIA (TBK) DALAM PEMBENTUKAN OPINI PUBLIK - Hamson, Zulkarnain; Lahi, Beddu; Nurdin, Nani Harlinda (Jurnal Dakwah Tabligh, 2021)
Public opinion is an opinion, idea, or idea issued by internal or external public parties of an organization or company regarding an issue that arises. The internal or external public party obtains information about a matter either face to face or through the mass media. The creation of public opinion that develops in both internal and external public circles can assist companies in evaluating work programs in achieving the company's vision, mission, and goals. Public opinion is formed and is positive due to the existence of an effective communication process. The objectives of this study were to identify the strategies undertaken by PT. Vale Indonesia Tbk. in building communication effectiveness. The location of this research was carried out in East Luwu District, South Sulawesi where the company operates. The research method used is a survey method with quantitative data supported by qualitative methods (Mixed method). The technique of determining respondents through the method of sampling Morgan and Krejci. The determination of informants was carried out using the snowball technique. The data obtained were analyzed quantitatively and qualitatively. Quantitative data analysis will be presented in the form of frequency tables and cross-tabulations, then qualitative data will be processed through three stages of analysis, namely data reduction, data presentation, and conclusion drawing. The results showed that the communication strategies and methods used in forming public opinion about the existence of the company and corporate social responsibility for the community were quite effective. So that a more optimal communication strategy is needed in order to create positive public opinion for both the company's existence and corporate social responsibility in the social, economic, and environmental aspects effectively.